The Comovement between Real Activity and Prices in the G7 - Wouter J. den Haan (Tinbergen Institute, 2002)
In this paper, we study the short-run and long-run comovement between prices and real activity in the G7 countries during the postwar period using vector autoregressive systems and frequency-domain filters. We find several patterns that are robust across countries and time periods. Typically, the correlation coefficients at long-run horizons are significantly negative and the correlation coefficients at short-run horizons are substantially higher. Additionally, there is evidence of positive correlation at short-run forecast horizons for some countries.
Keywords: E31; E37; 330; Comovement; vector autoregressive models.; Preisniveau; Bruttoinlandsprodukt; Konjunktur; Schätzung; G8-Staaten